Eduwisata Learning Planning Based on Sunan Muria Character Score in SD 3 Piji, Kudus District - Risalah Devi Anugrah (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2023)
The increasing penetration of foreign cultures has resulted in younger generations losing their identity and being prone to committing deviant actions. In dealing with this, educational institutions, especially schools, need to pass down the noble values that have been institutionalized in society as a reference for character building. The purpose of this research is to produce an educational learning model based on the character values of Sunan Muria which will be implemented in SD 3 Piji, Kudus Regency. This research is a field research using research and development methods. The stages of research carried out included: identification of learning needs at SD 3 Piji, development of learning models according to Sunan Muria's teachings, validation by teachers, field trials both in class and Piji Wetan Cultural Village and product revisions. The results showed that the educational learning model based on the character values of Sunan Muria was highly recommended because it was able to bring students closer to better understanding and preserving local wisdom in the surrounding environment. Students are indirectly directed to apply the character values they have acquired in everyday life. The educational learning model is also an innovative and fun learning method because it is not only concentrated in the classroom environment.